The influence of continuous prenatal exposure to valproic acid on physical, nociceptive, emotional and psychomotor responses during adolescence in mice: Dose-related effects within sexes - Podgorac, Jelena; Sekulić, Slobodan; Petković, Branka; Stojadinović, Gordana; Martać, Ljiljana; Pešić, Vesna (Frontiers in Behavioral Neuroscience, 2022)
Clinical findings show that the use of valproic acid (VPA) during pregnancy increases the risk of birth defects and autism spectrum disorder in offspring. Although there is a consensus that monitoring of potential long-term outcomes of VPA exposure is needed, especially in undiagnosed individuals, preclinical studies addressing this issue are rare. The present study examined the effects of continuous intrauterine exposure to a wide dose range of VPA (50, 100, 200 and 400 mg/kg/day) on the physical and behavioral response in peripubertal mice as a rodent model of adolescence. Body weight and the hot plate test (on postnatal days (PND) 25 and 32), the elevated plus-maze test (on PND35), and the open field test (on PND40) served to examine physical growth, the supraspinal reflex response to a painful thermal stimulus and conditional learning, anxiety-like/risk-assessment behavior, as well as novelty-induced psychomotor activity, respectively. VPA exposure produced the following responses: (i) a negative effect on body weight, except for the dose of 100 mg/kg/day in both sexes; (ii) an increase in the percentage of animals that responded to the thermal stimulus above the defined cut-off time interval and the response latency in both sexes; (iii) dose-specific changes within sexes in behavior provoked by a novel anxiogenic environment, i.e. in females less anxiety-like/risk-assessment behavior in response to the lowest exposure dose, and in males more pronounced anxiety-like/risk-assessment behavior after exposure to the highest dose and 100 mg/kg/day; (iv) dose-specific changes within sexes in novelty-induced psychomotor activity, i.e. in females a decrease in stereotypy-like activity along with an increase in rearing, and in males a decrease in stereotypy-like activity only. These findings show that continuous intrauterine exposure to VPA produces maladaptive functioning in different behavioral domains in adolescence and that the consequences are delicate to assess as they are dose-related within sexes.